After Civil Rights - JOHN D. SKRENTNY (Princeton University Press, 2013)
After spending several years researching and writing about the historical development of minority rights legislation in the United States, I learned something new. I learned that not everyone was as passionate about the history of American policy as I was. It turned out that many people were more interested in what was happening now, in the contemporary United States, than what had happened in the past. They wanted to know more about where we were going than about how we arrived at where we were. Eventually I came to share their interest. I had studied the history of affirmative action in employment for African-Americans in my first book, which focused on the years between 1965 and 1975. In my second, I sought to show how other groups won new rights during the same period, including nonblack racial minorities, women, immigrants, the disabled, and others. It makes sense now to write a third book to bring the story of minority rights development up to date, at least as it regards the important topic of employment, and as it regards people whom employers tend to categorize on the basis of their race, national origin, or immigrant status. More specifically, the purpose of this book is, first, to reveal changes that are going on in employment practices across a broad spectrum of job sectors as regards race. I call this management strategy racial realism. It refers to employer perceptions that workers vary by race in their ability to do certain jobs and contribute to organizational effectiveness, and/or in the kinds of signals their racial backgrounds send to customers and citizens. Though racial realism benefits whites, hardly anyone openly advocates for employers to manage their workplaces in ways that leverage whiteness. The racial realism that employers, advocates, activists, and political leaders regularly talk about is the kind that benefits nonwhites. A second goal of this book is to show how these employment practices are or (mostly) are not authorized by law, and to point some ways toward reform. I wish to show that despite the partisan nature of so many policy debates in America, these changes are not partisan, and that in words and actions, both political parties have shown support for them. In some small way, I hope also that by calling attention to these new realities, the book will encourage advocates to take true ownership of them—to acknowledge that they might claim to support color-blind classical liberalism in some contexts, but they also support racial realism, and to acknowledge that racial realism has downsides as well as upsides. Only then can we ensure that employment practices are in line with the consensus value of equal opportunity.